Public (Dis)Engagement in Toll Road Project: A Case Study from Indonesia - Nurhadi Susanto (Magister Administrasi Publik, 2019)
Although numerous studies have established the importance of public participation in development, in practice, the government or companies in charge of infrastructure development often obscure public perception about its potential impact on development outcomes. This research aims to provide a more detailed description of the impact of toll road construction projects with low public participation. This research is study is a case study that employed qualitative research design approach. The study provides a deeper understanding the impact that ignoring public engagement has on the construction toll road. Results of this study underscore the importance of participatory public project planning and implementation on project outcomes and impact. Specifically, results of the study showed that public disengagement in the construction of road toll impacts public perception [during the project preconstruction and construction stages; willingness to accept change in land use change that is necessary to realize the project; and ultimately the social impact of similar project. Study results are valuable inputs into decision making process on the need for participatory infrastructure development to enhance project acceptability, effectiveness and social impact; the importance of good development planning that involves taking into consideration all the scenarios during the implementation phase.